Infliximab Combined with Enteral Nutrition for Managing Crohn’s Disease Complicated with Intestinal Fistulas - Xiao-Li Wu; Ren-Pin Chen; Li-Ping Tao; Jian-Sheng Wu; Xiang-Rong Chen; Wei-Chang Chen (Gastroenterology Research and Practice)
Aim. This study was performed to evaluate the additional enteral nutrition (EN) in the efficacy of infliximab (IFX) compared with the conventional therapy in managing Crohn’s disease (CD) complicated with intestinal fistulas. Methods. A total of 42 CD with intestinal fistulas were randomly divided into infliximab treatment group (n=20) and conventional therapy group (n=22). We evaluated the laboratory indexes, Crohn’s disease activity index (CDAI), Crohn’s disease simplified endoscopic score (SES-CD), and healing of fistula in the two groups before treatment, at 14 weeks, and at 30 weeks, respectively. Results. In the IFX treatment group, the CDAI score, the SES-CD, erythrocyte sedimentation rate, and C-reactive protein levels were significantly decreased during treatment compared with those before treatment. The body mass index and albumin levels were increased in both groups. Moreover, in the IFX treatment group, fistula healing was found in 8 at the 14th week and 18 at the 30th week, respectively, which was greater than that in the conventional therapy group. Conclusion. Our study suggested that infliximab combined with EN is an effective treatment for CD patients complicated with intestinal fistulas.